Cyberbullying on Multicultural Education a Coastal Community Perspective: Systematic literature review - Susanti, Nanik; Adiyono, Soni; Romadhon, Zainur (Institut Teknologi Sepuluh Nopember, 2024)
This research explores the pervasive issue of cyberbullying, primarily targeting children and teenagers due to their close proximity to communication technologies. Cyberbullying manifests through various forms such as flaming, harassment, and identity impersonation, causing significant psychological and academic impacts on victims. The study, based on a selection of 30 Scopus publications, reveals that cyberstalking holds the highest classification at 90%, followed by flaming at 73%. The consequences of cyberbullying are classified into social (67%), psychological (63%), and academic (57%) impacts. The research emphasizes the need for specific knowledge about cyberbullying in coastal communities, where victims experience feelings of insecurity, isolation, and reduced academic concentration. The conclusion highlights the importance of raising awareness, implementing literacy programs, and enforcing regulations to combat cyberbullying, especially in the context of the Fourth Industrial Revolution. The findings provide valuable insights into the coastal community's perception of cyberbullying, urging parents to play an active role in safeguarding their children and promoting digital literacy.